Simultaneous Quantification of Main Saponins in Panax vietnamensis by HPLC-PDA/ELSD Using the Quantitative Analysis of Multi-Components by Single-Marker Method - Thi-My-Duyen Ngo; Thi Kim Ngan Tran; Thi Minh Thu Le; Mong Kha Tran; Huu Son Nguyen; Huy Truong Nguyen; Kim Long Vu-Huynh (Metabolites, 2025)
Background: The Quantitative Analysis of Multi-components by Single-marker (QAMS) method has been developed as an alternative to the External Standards Method (ESM) for the quality control of medicinal herbs. Objectives: In this study, QAMS was developed to determine saponins in the raw materials of Panax vietnamensis using HPLC-PDA/ELSD. Methods: The method was developed and validated. The relative conversion factors Fx were calculated based on the linear regression for HPLC-PDA and the logarithm equation for HPLC-ELSD. The Standard Method Difference (SMD) was determined to indicate the difference in the results of QAMS and EMS. Results: Relative conversion factors (Fx) were determined for each detector to quantify five saponins (ginsenoside Rb1, Rd, Rg1, majnoside R2, and vina-ginsenoside R2) in VG root. The Fx values were calculated based on the ratio of the slopes of the regression equations of a single standard and an external standard. For HPLC-PDA, G-Rb1 was used as a single standard with the Fx values of 1.00 (G-Rb1), 1.08 (G-Rd), 1.32 (G-Rg1), and 0.04 (M-R2). For HPLC-ELSD, G-Rb1 was used for determining the content of G-Rg1 and G-Rb1 with the Fx values of 1.00 (G-Rb1) and 0.95 (G-Rg1), while M-R2 was used for quantitating M-R2 and V-R2 with Fx of 1.00 (M-R2) and 1.05 (V-R2). An SMD value less than 5.00% confirms the close alignment of the QAMS method with ESM. Conclusions: The QAMS method proved to be a feasible and promising method for the quality control of P. vietnamensis.